PENERAPAN METODE LATIHAN TERHADAP PERCEPATAN KEMAMPUAN MEMBACA DAN MEMAINKAN DI SMP NEGERI 1 BUKITTINGGI - Rahmania Rahmania; Jagar Lumban Toruan; Yos Sudarman (SENDRATASIK UNP, 2013)
Abstract   This research was aimed at describing the implementation of drill method in increasing the students’ abilities to read and play the rhythm. This research was a qualitative one. The results of the research have explained some rhythm drills as follows: (1) drill of the basic tempo, (2) the form of foot and hands gestures and rhythmic syllables, (3) how to read rhythm patterns using gestures, and (4) train students to read the songs partiture with the appropriate rhythm.  It has been proven that drill method can increase the students’ ability to read the rhythm and the notation appropriately, especially for the students of VIIIB at SMPN 1 Bukittinggi. Keywords : qualitative study, drill method, rythm.